Omni-channel strategy for an online retailer: considering experience service and shopping costs. Issue 2 (3rd May 2021) - Liu, Jinrong; Xu, Qi; Zhang, Guoqing
Abstract: Retailers are increasingly offering customers a seamless shopping experience through all available shopping channels. However, when should an online retailer open an offline showroom or a physical store to implement an omni-channel strategy? In this study, we establish profit models in four scenarios and obtain the conditions under which an online retailer can be profitable in different channels. The results show that, after opening a showroom or store, demand in the online channel decreases and total demand increases. Furthermore, the choice of opening a showroom or a physical store depends on the online return rate and the unit inventory holding costs of the online and offline channels. In addition, if the perceived experience service is not too high, the total profit after opening a showroom or store increases with the experience service and the shopping cost of the online channel. Furthermore, the growth rate with a showroom is higher than that with a store.